2020
DOI: 10.1186/s13063-020-04678-4
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin for primary thromboprophylaxis in ambulatory patients with coronavirus disease-2019 (the OVID study): a structured summary of a study protocol for a randomized controlled trial

Abstract: Objectives The OVID study will demonstrate whether prophylactic-dose enoxaparin improves survival and reduces hospitalizations in symptomatic ambulatory patients aged 50 or older diagnosed with COVID-19, a novel viral disease characterized by severe systemic, pulmonary, and vessel inflammation and coagulation activation. Trial design The OVID study is conducted as a multicentre open-label superiority randomised controlled trial. Participants Inclusion Criteria 1. Signed patient informed consent after being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…A spectrum of anticoagulants such as unfractionated Heparin, Enoxaparin, and Rivaroxaban are being used in COVID-19 patient management as needed [ 8 , 9 ]. A clinical trial is being designed to examine whether prophylactic-dose Enoxaparin improves survival and reduces hospitalizations in older (age > 50) symptomatic ambulatory patients [10] . Recent in vitro studies have shown that pseudotyped viral particles were efficiently neutralized by a variety of anticoagulants [11] .…”
Section: Introductionmentioning
confidence: 99%
“…A spectrum of anticoagulants such as unfractionated Heparin, Enoxaparin, and Rivaroxaban are being used in COVID-19 patient management as needed [ 8 , 9 ]. A clinical trial is being designed to examine whether prophylactic-dose Enoxaparin improves survival and reduces hospitalizations in older (age > 50) symptomatic ambulatory patients [10] . Recent in vitro studies have shown that pseudotyped viral particles were efficiently neutralized by a variety of anticoagulants [11] .…”
Section: Introductionmentioning
confidence: 99%
“…PREVENT-HD is one of a limited number of placebo-controlled trials registered on clinicaltrials.gov examining antithrombotic interventions in outpatients with COVID-19. A smaller trial (n=600) is also evaluating rivaroxaban vs placebo in outpatients (NCT04504032), while one larger outpatient primary thromboprophylaxis trial (the OVID trial, NCT04400799) is comparing enoxaparin 40mg SQ daily vs placebo (N=1000) ( 51 ). The National Institute of Health trial [NCT04498273] is randomizing to one of four arms (N=7000): apixaban 2.5mg bid, apixaban 5mg bid, low-dose aspirin once daily, or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome for the COVID-PREVENT, HERO-19 and CONVINCE trials is the composite of mortality and arterial and venous thromboembolism; the primary outcome for the randomized double-blind placebo controlled ACTIV-4b trial is a composite of venous and arterial thromboembolism, hospitalization for cardiovascular/pulmonary events and all-cause mortality. ETHIC and OVID RCTs are comparing the effect of standard prophylactic dose of enoxaparin versus no intervention on the primary outcome of hospitalization or mortality in 2,370 individuals (41).…”
Section: Review Of Ongoing or Completed Randomized Controlled Trialsmentioning
confidence: 99%